RESPOSTAS DA PRESSÃO SISTÓLICA ARTERIAL PULMONAR EM INDIVÍDUOS COM DOENÇA PULMONAR OBSTRUTIVA CRÔNICA E PORTADORES DE DEFICIÊNCIA FÉRRICA SEM ANEMIA DURANTE O ESTRESSE FARMACOLÓGICO COM DOBUTAMINA - Ana Christina Wanderley Xavier (2022)
Non-anemic iron deficiency (NAID) can increase pulmonary artery pressure in patients with chronic obstructive pulmonary disease (COPD). The association between NAID and COPD has been widely reported, with pulmonary arterial hypertension (PAH) manifesting as a frequent complication of COPD. With the use of echocardiograms, systolic pulmonary artery pressure (SPAP) can be estimated from maximum systolic velocity of tricuspid regurgitation to determine right ventricular systolic pressure. Studies have shown that pharmacological stress echocardiography with dobutamine (DSE) is a safe procedure for COPD patients. For the present study, SPAP responses in COPD and NAID patients under ambient oxygen conditions were recorded before (at rest) and at peak DSE (associated or otherwise with atropine and isometric handgrip exercise). This single-center, parallel-group, observational, prospective study drew on primary data from 24 outpatients aged 45-85 years presenting with GOLD stages II-IV COPD, comprising 10 individuals with positive iron deficiency (NAID+) and 14 with negative iron deficiency (NAID–). Of the variables observed in the echocardiograms, only left atrium volume indexed to body surface (LAVi; mL/m²) differed significantly (p = 0.002) between groups (30±4 for NAID+ vs. 23±5 for NAID–). Study of right heart chambers revealed similar tricuspid annular plane systolic excursion (TAPSE; mm) at rest (p > 0.05) in both groups (22±2 vs. 20±4, respectively). There was no significant difference in SPAP changes (mmHg) between groups before and at peak DSE (NAID+: 32±14 vs. 48±14, respectively; NAID–: 29±7 vs. 43±10, respectively; pgroup = 0.400; ptime < 0.0001; pinteraction = 0.606). In conclusion, COPD patients with NAID+ did not exhibit greater increase in SPAP at peak DSE compared with NAID– subjects.